2021
DOI: 10.7705/biomedica.5898
|View full text |Cite
|
Sign up to set email alerts
|

Association of VDR gene ApaI polymorphism with obesity in Iranian population

Abstract: Introduction: Identifying the risk factors of obesity as a problem facing communities is crucial given its complexity. The vitamin D receptor (VDR) gene has been reported as a candidate for this disease in literature. Objective: To investigate the association of ApaI, BsmI and TaqI polymorphisms of VDR gene with obesity in part of Iranian population. Material and methods: In this study, genotypes of 348 obese (BMI ≥30 kg/m2) and 320 non-obese (BMI: 18.5-24.9 kg/m2) were analyzed by using PCR-RFLP m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…For this reason, the gene encoding VDR is considered an important candidate for the genetic regulation of bone strength, bone homeostasis, and metabolism. The approximately 75 kb gene is located on chromosome 12q13.11, containing 12 exons and nearly 300 different polymorphisms [13,14]. Variability in the VDR gene has been identified as a possible contributor to OP.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the gene encoding VDR is considered an important candidate for the genetic regulation of bone strength, bone homeostasis, and metabolism. The approximately 75 kb gene is located on chromosome 12q13.11, containing 12 exons and nearly 300 different polymorphisms [13,14]. Variability in the VDR gene has been identified as a possible contributor to OP.…”
Section: Introductionmentioning
confidence: 99%
“…A study from Iran which looked at the association of the VDR gene ApaI, BsmI, and TaqI polymorphisms with obesity in 348 obese and 320 non-obese subjects reported an increased risk of obesity in subjects with VDR ApaI polymorphism. In particular, the A allele and the AA genotype in ApaI were associated with the obesity phenotypes [ 30 ]. Another systematic review of the association between genetic polymorphisms and obesity in the Arab world included 59 studies with a total of 15,488 cases and 9760 controls in the final analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Their results indicated that the VDR ApaI polymorphism and obesity susceptibility, whereas the ApaI A allele and AA genotype, were related to obesity phenotypes. The higher serum levels of FBS and BMI in genotype AA carriers provided clear evidence of the associations between the VDR gene polymorphisms and the anthropometric and biochemical characteristics of obesity 5 . In our recent study, positive ndings in polymorphisms of vitamin D-related genes were obtained.…”
Section: The Association Of Vitamin D Levels and Vitamin D Receptor G...mentioning
confidence: 92%
“…VDR gene has been reported to be signi cantly associated with obesity among the Iranian population 5 .…”
Section: Introductionmentioning
confidence: 99%